Pengaruh Citra Merek Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Hand & Body Lotion Citra (Studi pada Mahasiswi Fakultas Ekonomi Bisnis Prodi Manajemen Angkatan 2018-2020 di Universitas Muhammadiyah Bandung) - Awalia, Neng Irma; Fitriani, Iis Dewi; Andriyani, Yeni (Jurnal Manajemen DIVERSIFIKASI, 2023)
This study aims to determine whether Brand Image and Product Quality affect the PurchaseDecision of Hand & Body Lotion Citra (Study on Students of the Business Economics Facultyof Management Study Program Class of 2018- 2020 at the University of MuhammadiyahBandung). The method used in this study is a quantitative approach, by using this researchmethod it will be known that there is a significant relationship between the variables studiedso that conclusions will clarify the description of the object under study. Based on the resultsof the study, the results of multiple linear regression analysis were obtained, the regressionequation was obtained as follows: Y = 8.493 + 0.266X1 + 0.336X2.. Brand Image andQuality Influence on Purchase Decisions for Hand & Body Lotion Citra (Study on Students ofthe Business Economics Faculty of Management Study Program Class of 2018- 2020 at theUniversity of Muhammadiyah Bandung) imultaneous contribution of 39.3% to purchasingdecisions. While the remaining 0.607 or 60.7% is influenced by other variables such as price,promotion and place which were not examined by the author.